Modelling and optimization of a wellhead gas flowmeter using concentric pipes. Issue 9 (2nd September 2017) - Nec, Yana; Huculak, Greg
ABSTRACT: A novel configuration of a landfill wellhead was analysed to measure the flow rate of gas extracted from sanitary landfills. The device provides access points for pressure measurement integral to flow rate computation similarly to orifice and Venturi meters, and has the advantage of eliminating the problem of water condensation often impairing the accuracy thereof. It is proved that the proposed configuration entails comparable computational complexity and negligible sensitivity to geometric parameters. Calibration for the new device was attained using a custom optimization procedure, operating on a quadri-dimensional parameter surface evincing discontinuity and non-smoothness.